Bringing Stellar Evolution and Feedback Together: Summary of Proposals from the Lorentz Center Workshop. (9th March 2023) - Geen, Sam; Agrawal, Poojan; Crowther, Paul A.; Keller, B. W.; de Koter, Alex; Keszthelyi, Zsolt; van de Voort, Freeke; Ali, Ahmad A.; Backs, Frank; Bonne, Lars; Brugaletta, Vittoria; Derkink, Annelotte; et al.
Abstract: Stars strongly impact their environment, and shape structures on all scales throughout the universe, in a process known as "feedback." Due to the complexity of both stellar evolution and the physics of larger astrophysical structures, there remain many unanswered questions about how feedback operates and what we can learn about stars by studying their imprint on the wider universe. In this white paper, we summarize discussions from the Lorentz Center meeting "Bringing Stellar Evolution and Feedback Together" in 2022 April and identify key areas where further dialog can bring about radical changes in how we view the relationship between stars and the universe they live in.